Electrode Behavior RE-Visited: Monitoring Potential Windows, Capacity Loss, and Impedance Changes in Li1.03(Ni0.5Co0.2Mn0.3)0.97O2/Silicon-Graphite Full Cells. Issue 6 (1st January 2016) - Klett, Matilda; Gilbert, James A.; Trask, Stephen E.; Polzin, Bryant J.; Jansen, Andrew N.; Dees, Dennis W.; Abraham, Daniel P.
Abstract : The capacity and power performance of lithium-ion battery cells evolve over time. The mechanisms leading to these changes can often be identified through knowledge of electrode potentials, which contain information about electrochemical processes at the electrode-electrolyte interfaces. In this study we monitor electrode potentials within full cells containing a Li1.03 (Ni0.5 Co0.2 Mn0.3 )0.97 O2 –based (NCM523) positive electrode, a silicon-graphite negative electrode, and an LiPF6 -bearing electrolyte, with and without fluoroethylene carbonate (FEC) or vinylene carbonate (VC) additives. The electrode potentials are monitored with a Li-metal reference electrode (RE) positioned besides the electrode stack; changes in these potentials are used to examine electrode state-of-charge (SOC) shifts, material utilization, and loss of electrochemically active material. Electrode impedances are obtained with a Lix Sn RE located within the stack; the data display the effect of cell voltage and electrode SOC changes on the measured values after formation cycling and after aging. Our measurements confirm the beneficial effect of FEC and VC electrolyte additives in reducing full cell capacity loss and impedance rise after cycling in a 3.0–4.2 V range. Comparisons with data from a full cell containing a graphite-based negative highlight the consequences of including silicon in the electrode. Our observations on electrode potentials, capacity, and impedance changes on cycling are crucial to designing long-lasting, silicon-bearing, lithium-ion cells.